Loss of longline-bait to northern fulmars : economic balance between damage from bait-loss and costs of measures to reduce seabird bycatch on the Faroe Islands - Kühn, Susanne, 1987- (2016)
Verkefnið er unnið við Háskólasetur Vestfjarða On the Faroe Islands, longline fishermen experience a loss of bait to scavenging seabirds. This Master thesis evaluates the economic impact of bait-stealing by a seabird, the northern fulmar (Fulmarus glacialis), in the longline fisheries. Baits found in stomachs of northern fulmars, caught accidentally in longline fisheries around the Faroe Islands, were used to estimate the bait loss. From this an estimate was made of the potential economic loss experienced by fishermen due to seabirds. Possible mitigation measures were discussed regarding their suitability for the Faroese fisheries and their economic viability. The results show that the economic loss for the fishermen can range between 600 and 88,000 Danish Krona (DKK) per trip for one vessel, depending on the fishing efficiency and the number of birds surrounding the vessel. As a mitigation measure, tori lines are proposed to keep the birds out of the reach of bait. It became clear that direct observer data is necessary to evaluate the situation on the Faroe Islands and to make a realistic picture of the extent of the fisheries-seabird interaction. Unfortunately the collection of data on board of fishing vessels was beyond the scope of this thesis. Nevertheless a useful tool is provided for fishermen to calculate the individual economic loss they suffer from seabirds and weigh the financial loss of seabirds stealing baits against the costs of mitigation measures that might reduce seabird fatalities and therefore create a situation where both, fishermen and seabirds benefit.